STRATEGY FOR DEVELOPING A SUSTAINABLE AND INCLUSIVE ECONOMY BASED ON REGIONAL EMPOWERMENT IN PANGKEP REGENCY - A Nursyamsi Amin; Andira; Qonitah Marwah S.; Ananda Tri Ambarwati (Applied Accounting and Management Review (AAMAR), 2026)
The fluctuations of the Indonesian economy require the government to implement strategies to address them as an effort to realize an inclusive and sustainable economy in the future to improve the welfare of the community. Pangkep Regency is one of the regions in South Sulawesi that has unique characteristics, including its archipelagic areas, distinctive mountains, and land surrounded by natural resources. However, the reality is that this regency ranks first as the poorest regency in South Sulawesi according to the Central Statistics Agency of South Sulawesi 2023. This condition is in stark contrast to the actual situation on the ground, as the largest cement factory in eastern Indonesia is located in this area. This research is a qualitative study with an ethnographic approach, involving interviews with the community in the area and linking it to literature review. The research results in two main strategies: the empowerment of the surrounding environment and the concept of using technology that can be applied to promote the economy of Pangkep Regency.